2016
DOI: 10.1590/s1984-29612016007
|View full text |Cite
|
Sign up to set email alerts
|

Acanthocephala Larvae parasitizing Ameiva ameiva ameiva (Linnaeus, 1758) (Squamata: Teiidae)

Abstract: Knowledge concerning the taxonomy and biology of species of Acanthocephala, helminth parasites of the helminth species of the phylum Acanthocephala, parasites of lizards in Brazilian Amazonia, is still insufficient, but reports of Acanthocephala in reptiles are becoming increasingly common in the literature. Cystacanth-stage Acanthocephalan larvae have been found in the visceral peritoneum during necropsy of Ameiva ameiva ameiva lizards from the "Osvaldo Rodrigues da Cunha" Herpetology Collection of the Emílio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The previous studies have reported similar findings of the cystacanth stage infecting various species of reptiles, such as rainbow lizards ( Mabuya quinquetaeniata ), ameiva lizards ( Ameiva ameiva ), and coastal clawed geckos ( Gonatodes antillensis ). Moreover, the predilection of cystacanth has also been reported in various body cavities, including subcutaneous tissues, causing nodules as a pathological sign [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have reported similar findings of the cystacanth stage infecting various species of reptiles, such as rainbow lizards ( Mabuya quinquetaeniata ), ameiva lizards ( Ameiva ameiva ), and coastal clawed geckos ( Gonatodes antillensis ). Moreover, the predilection of cystacanth has also been reported in various body cavities, including subcutaneous tissues, causing nodules as a pathological sign [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particular emphasis should be placed on exploring potential paratenic hosts, as the existing research landscape points to the prevalence of the cystacanth stage in various reptile species (Dornburg et al 2019). Examples include ameiva lizards (Ameiva ameiva), rainbow lizards (Mabuya quinquetaeniata), and coastal clawed geckos (Gonatodes antillensis), as elucidated in studies by Rabie et al (2015), Macedo et al (2016), and Dornburg et al (2019).…”
Section: The Prevalence Of Acanthocephalan In Naja Sputatrix Snakesmentioning
confidence: 99%